ENERGY SECURITY AS THE MAIN COMPONENT OF CROSS-BORDER COOPERATION IN THE FRAMEWORK OF THE CARPATHIAN EUROREGION - Verbovska, L.S. (The actual problems of regional economy development, 2016)
This article is devoted to the problems of effective functioning of cross-border cooperation as a major factor in the impact of the international cooperation in energy independence within the Carpathian Euroregion. The study found that the Ukrainian gas transport system is of strategic importance, based on which it is possible to create a gas exchange, allows you to save your own potential and national priorities. The variants of the use of the gas transportation system of Ukraine to the use and transportation of oil and gas within the Carpathian Euroregion. JEL: R 13